2019
DOI: 10.1007/s11192-019-03155-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender gaps in international research collaboration: a bibliometric approach

Abstract: This paper addresses gender differences in international research collaboration measured through international co-authorship. The study is based on a dataset consisting of 5600 Norwegian researchers and their publication output during a 3-year period (44,000 publications). Two different indicators are calculated. First, the share of researchers that have been involved in international collaboration as measured by co-authorship, and second, the share of their publications with international co-authorship. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 33 publications
(46 reference statements)
4
42
1
3
Order By: Relevance
“…Our findings support conclusions drawn by Abramo et al (2013) about Italian scientists: male scientists exhibit higher collaboration rates in international collaboration. Our findings do not, however, support conclusions from Aksnes et al (2019), who found that gender is not an important determinant of international research collaboration. Consequently, in the Polish case, women's progression on the academic ladder is likely to be more difficult and more protracted, with less access to increasingly competitive individual research funding.…”
Section: Summary Discussion and Conclusioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings support conclusions drawn by Abramo et al (2013) about Italian scientists: male scientists exhibit higher collaboration rates in international collaboration. Our findings do not, however, support conclusions from Aksnes et al (2019), who found that gender is not an important determinant of international research collaboration. Consequently, in the Polish case, women's progression on the academic ladder is likely to be more difficult and more protracted, with less access to increasingly competitive individual research funding.…”
Section: Summary Discussion and Conclusioncontrasting
confidence: 99%
“…In Norway, Aksnes et al (2019) used the Cristin bibliographic database (Norwegian Science Index of all peer-reviewed publications) to study gender differences in international collaboration across the four largest universities. Again, the unit of analysis was the individual scientist; counting all individuals equally as single units, regardless of productivity (Aksnes et al 2019: 8), limited the effect of the outliers present in all systems.…”
Section: International Research Collaboration and Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…When identical curriculum vitae are reviewed, more significant opportunity belongs to male job applicants who were considered to have adequate teaching, research, and service experiences (Steinpreis, Anders, & Ritzke, 1999). Corresponding to the underrepresentation at every academic level (Hopkins, Jawitz, McCarty, Goldman, & Basu, 2013) including Ph.D. enrolment (Hernánde‐Martín, Calle, Dueñas, Holgado, & Gómez‐Pérez, 2019), women are fewer in decision‐making designation (Hopkins et al, 2013), academic promotion (Carter, Smith, & Osteen, 2017), permanent position (Bailey et al, 2017), international research collaboration (Aksnes et al, 2019; Paul‐Hus et al, 2015) and other aspects. In terms of wages, awards, equipment, and invitations as keynote speakers at essential conferences, women are also at the disadvantage position (Lincoln, Pincus, Koster, & Leboy, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Por razões históricas e culturais, há um desequilíbrio na participação de homens e mulheres na educação e na carreira de diversasáreas. De fato, na Academia, as diferenças são significativas na autoria de artigos [Arruda et al 2009, Mihalcea andWelch 2015] e na colaboração internacional [Aksnes et al 2019]. Tal falta de diversidade de gênero impacta a produtividade [Turban et al 2019], e na Computação nãoé diferente.…”
Section: Introductionunclassified